Whole Genome Sequencing and Assembly of the Asian Honey Bee Apis dorsata. (20th December 2019) - Oppenheim, Sara; Cao, Xiaolong; Rueppel, Olav; Krongdang, Sasiprapa; Phokasem, Patcharin; DeSalle, Rob; Goodwin, Sara; Xing, Jinchuan; Chantawannakul, Panuwan; Rosenfeld, Jeffrey A
Abstract: The Asian honey bee ( Apis dorsata ) is distinct from its more widely distributed cousin Apis mellifera by a few key characteristics. Most prominently, A. dorsata, nest in the open by forming a colony clustered around the honeycomb, whereas A. mellifera nest in concealed cavities. Additionally, the worker and reproductive castes are all of the same size in A. dorsata . In order to investigate these differences, we performed whole genome sequencing of A. dorsata using a hybrid Oxford Nanopore and Illumina approach. The 223 Mb genome has an N50 of 35 kb with the largest scaffold of 302 kb. We have found that there are many genes in the dorsata genome that are distinct from other hymenoptera and also large amounts of transposable elements, and we suggest some candidate genes for A. dorsata' s exceptional level of defensive aggression.